Proportion of fever attributable to malaria in Colombia: Potential indicators for monitoring progress towards malaria elimination (2017)
Objective Identify and characterize indicators  to assess progress in terms of control and monitoring of malaria in endemic areas of Colombia and compare malaria elimination findings with those of countries in the same region.Methods Cross-sectional surveys were carried out in 2011 and 2014 in malaria endemic areas in Colombia, Pacific and Caribbean regions. A socio-demographic and a clinical questionnaire were applied to each participant; likewise, written and informed consents were obtained. Capillary blood samples were taken and examined through microscopic tests and rapid diagnostic test. A narrative systematic review was conducted to correlate malaria elimination in Colombia and in countries of the Amazon Region.Results The sample consisted of 548 participants from the departments of Córdoba and Nariño, Colombia. The proportion of positive malaria cases was 3 % (17/548), in which the prevalence of malaria mixed infections was 47 % (8/17). Regarding fever, temperature over 38.0o C, its prevalence was 2.7 % (15/548). Only two febrile patients tested positive for the disease. Prevalence of asymptomatic malaria cases among all positive cases was 88 %.Conclusion Asymptomatic malaria cases, mixed infections and self-medication are the challenges that malaria control and elimination programs face. It is important to note that studies on subclinical malaria in the region are scarce. Endemic areas with dense populations and experiencing an increase in immigration levels are more vulnerable to malaria reemergence. Imported malaria cases impact the basic reproduction rate (Ro). Funding resources availability has impact on the sustainability of public health actions and the elimination of malaria in South America.